Faktor-faktor yang Mempengaruhi Keberhasilan Ibu Hamil dalam Pemeriksaan Antenatal Care di Desa Cikunir - Rhela Panji; Resita Indriyani Dewi; Winda Astria Putri (Jurnal Kebidanan Besurek, 2026)
Antenatal care (ANC) is an essential health service for pregnant women to monitor pregnancy conditions and detect potential complications at an early stage. However, the utilization of ANC services in several regions remains suboptimal, including in Tasikmalaya Regency. Health Office data showed that while the first antenatal visit (K1) coverage increased, the fourth visit (K4) coverage declined, indicating that some pregnant women had not completed antenatal examinations according to the recommended standards. This study aimed to identify factors influencing the success of ANC visits among pregnant women in Cikunir Village, Tasikmalaya Regency. This research employed a quantitative analytic design with a cross-sectional approach. The sampling technique used total sampling, involving 20 pregnant women as respondents. Data were collected using questionnaires covering age, education, occupation, level of awareness, barriers to health services, and family support related to ANC visit compliance. Data analysis was conducted using univariate and bivariate analyses with the Fisher Exact test at a significance level of α = 0.05. The results showed that most respondents were within the safe reproductive age group (70%), had middle to higher educational levels (65%), were unemployed (60%), experienced no barriers in accessing health services (90%), and attended ANC visits accompanied by their husbands (95%). A total of 85% of respondents successfully completed ANC visits according to the standard. Bivariate analysis revealed significant relationships between age, education, barriers to health services, and husband’s support with the success of ANC visits among pregnant women.